The Effect of Income Level on the Financial Behavior of Micro, Small and Medium Enterprises in Lubuklinggau City - suyadi suyadi; Irma Idayati; Eri Triharyati; Fitria Fitria; Hardi Mulyono (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2023)
This research was conducted to see The Effect of Income Level on the Financial Behavior Usaha Mikro Kecil dan Menengah di Kota Lubuklinggau. Sampling, using a purposive side. The number of samples was 98 respondents. The analysis tool used was SEM which was run with SmatPLS3.0 software. The results of this study are related to the theme of Influence of Income Level on the The Effect of Income Level on the Financial Behavior Usaha Mikro Kecil dan Menengah di Kota Lubuklinggau.The number of samples in this study used 98 respondents of Micro, Small and Medium Enterprises (MSMEs) in Lubuklinggau with the willingness of respondents to fill out questionnaires with valid data totaling 89 respondents. After testing, it can be concluded that: This study found that income levels had a positive effect on financial behavior. This was due to the results of testing the hypothesis which shows that the income level with financial behavior shows the path coefficient value of the original sample estimate of 0.451 with a significance below 5% which is indicated by the t-statistic value of 5.625 which is greater than the t-table value of 1.984. the P-Value is 0.000. P-value (0.000) < α = 5 This study found that the level of income has a positive effect on financial behavior. This means that the higher the level of income, the better the financial behavior will be and this will have an impact on better financial management. This study made modifications to the data testing because there were several indicator results that did not meet the requirements so dropping or elimination had to be carried out on each variable indicator that did not meet the discriminant validity requirements. This research was useful for the academic environment and MSME managers in Lubuklinggau